Progress in three‐dimensional computed tomography reconstruction in anatomic pulmonary segmentectomy. Issue 13 (18th May 2022) - Wu, Zhe; Huang, Zhangfeng; Qin, Yi; Jiao, Wenjie
Abstract: The number of minimally invasive surgeries, such as video‐assisted thoracoscopic surgery and robot‐assisted thoracoscopic surgery, has increased enormously in recent years. More and more relevant studies report that anatomic pulmonary segmentectomy has the same effect as traditional lobectomy in the surgical treatment of early stage non‐small cell lung cancer (diameter less than 2.0 cm). Segmentectomy requires sufficient knowledge of the location of the pulmonary nodules, as well as the anatomy of the target segments, blood vessels, and bronchi. With the rapid development of imaging technology and three‐dimensional technology, three‐dimensional reconstruction has been widely used in the medical field. It can effectively assess the vascular branching patterns, discover the anatomic variations of the blood vessels and bronchi, determine the location of the lesion, and clarify the division of the segments. Therefore, it is helpful for preoperative positioning, surgical planning, preoperative simulation and intraoperative navigation, and provides a reference for formulating an individualized surgical plan. It therefore plays a positive role in anatomic pulmonary segmentectomy. This study reviews the progress made in three‐dimensional computed tomography reconstruction in anatomic pulmonary segmentectomy. Abstract : Three‐dimensional reconstruction can effectively assess the vascular branching patterns, discover the anatomic variations of the blood vessels and bronchi, determine the location of the lesion, and clarify the division of the segments. It is helpful for preoperative positioning, surgical planning, preoperative simulation and intraoperative navigation, which provides a reference for formulating an individualized surgical plan. It plays a positive role in anatomic pulmonary segmentectomy.